Equilibria in acetone medium. IX. The peculiar behaviour of the Cobalt (II) chloride-pyrazole system - Molina, Manuel; de Moraes, Mercedes; Melios, Cristo Bladimiros; Tognolli, João Olímpio (Eclética Química, 1981)
.